Korean Medication Algorithm for Schizophrenia 2019, Second Revision: Treatment of Psychotic Symptoms - Lee, Jung Suk; Yun, Je-Yeon; Kang, Shi Hyun; Lee, Seung Jae; Choi, Joon-Ho; Nam, Beomwoo; Lee, Seung-Hwan; Chung, Young-Chul; Kim, Chan-Hyung (Clinical psychopharmacology and neuroscience : the official scientific journal of the Korean College of Neuropsychopharmacology, 2020)
In 2001, the Korean College of Neuropsychopharmacology and the Korean Society for Schizophrenia Research developed the Korean Medication Algorithm Project for Schizophrenia (KMAP-SPR 2001, revised 2006) through a consensus of expert opinion. The present study was carried out to support the second revision of the KMAP-SPR.ObjectiveIn 2001, the Korean College of Neuropsychopharmacology and the Korean Society for Schizophrenia Research developed the Korean Medication Algorithm Project for Schizophrenia (KMAP-SPR 2001, revised 2006) through a consensus of expert opinion. The present study was carried out to support the second revision of the KMAP-SPR.Based on clinical guidelines and studies on the treatment of psychotic symptoms in schizophrenia, the Executive committee completed a draft of KMAP-SPR 2019. To obtain an expert consensus, a Review committee of 100 Korean psychiatrists was formed and 69 responded to a 30-item questionnaire. Based on their responses, the KMAP-SPR 2019 was finalized.MethodsBased on clinical guidelines and studies on the treatment of psychotic symptoms in schizophrenia, the Executive committee completed a draft of KMAP-SPR 2019. To obtain an expert consensus, a Review committee of 100 Korean psychiatrists was formed and 69 responded to a 30-item questionnaire. Based on their responses, the KMAP-SPR 2019 was finalized.The revised schizophrenia algorithm now consists of 5 stages. At Stage 1, monotherapy with atypical antipsychotics was recommended by expert reviewers as the first-line strategy. At Stage 2, most reviewers recommended the use of typical or atypical antipsychotic drugs not used at Stage 1. At Stage 3, many reviewers agreed with the administration of clozapine. At Stage 4, a combination of clozapine and other agents such as antipsychotics, mood stabilizers, antidepressants, or electroconvulsive therapy was recommended. At Stage 5, most reviewers recommended combined treatment with an antipsychotic other than clozapine; and a mood stabilizer, antidepressant, or electroconvulsive therapy. At any stage, prescribing long-acting injectable antipsychotics at the discretion of the clinician was recommended.ResultsThe revised schizophrenia algorithm now consists of 5 stages. At Stage 1, monotherapy with atypical antipsychotics was recommended by expert reviewers as the first-line strategy. At Stage 2, most reviewers recommended the use of typical or atypical antipsychotic drugs not used at Stage 1. At Stage 3, many reviewers agreed with the administration of clozapine. At Stage 4, a combination of clozapine and other agents such as antipsychotics, mood stabilizers, antidepressants, or electroconvulsive therapy was recommended. At Stage 5, most reviewers recommended combined treatment with an antipsychotic other than clozapine; and a mood stabilizer, antidepressant, or electroconvulsive therapy. At any stage, prescribing long-acting injectable antipsychotics at the discretion of the clinician was recommended.Compared with previous versions, the KMAP-SPR 2019 now recommends using clozapine earlier in treatment- refractory schizophrenia. In addition, the use of long-acting injectable antipsychotics is now considered to be available at any stage.ConclusionCompared with previous versions, the KMAP-SPR 2019 now recommends using clozapine earlier in treatment- refractory schizophrenia. In addition, the use of long-acting injectable antipsychotics is now considered to be available at any stage.